Affective Interventions on the Maternal Archive in "La Caja Topper" by Nicolás Gadano (Anclajes, 2021)
Through the study of the autobiographical novel La caja Topper by Nicolás Gadano (2019), this article addresses the uses of the archive in the narratives of the children of victims ––in a broad sense–– of the last Argentine military dictatorship. Following the theoretical propositions of Jacques Derrida, Sara Ahmed, and Adriana Cavarero, we analyze the interventions that Gadano makes on the objects that his mother kept in a sneaker box as memorabilia of the family exile experience. First, we study the way in which the old box and the objects contained in it function as a matriarchive. Second, we analyze the operations that Gadano performs on the materiality, content, and ordering of the objects in the box, which produces a generational transfer of authority over the archive. Finally, we conclude that, through his fidelity to the maternal affective style, the author disassembles the traditional model of emotional labor division, reshaping the links between gender, generations, and memory.
Keywords: Argentina; 21st Century; Memory; Generations; Archive